2015
DOI: 10.1515/cclm-2014-1039
|View full text |Cite
|
Sign up to set email alerts
|

Role of vitamin D and sFlt-1/PlGF ratio in the development of early- and late-onset preeclampsia

Abstract: Low vitamin D status in women with suspected late-onset PE increases the risk of imminent development of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…In our study setting, one of the common indications for caesarean section is pre-eclampsia, the prevalence of which has been associated with VDD. [39][40][41] The low…”
Section: Research Discussionmentioning
confidence: 99%
“…In our study setting, one of the common indications for caesarean section is pre-eclampsia, the prevalence of which has been associated with VDD. [39][40][41] The low…”
Section: Research Discussionmentioning
confidence: 99%
“…In a prospective study, biochemical and/or biophysical markers of PE development did not differ among first trimester gravidae with or without low vitamin D status [ 43 ]. Nonetheless, retrospective analysis has shown an increased risk of late-onset, but not early-onset, PE among women with low vitamin D status at clinical presentation despite no difference in first trimester 25(OH)D concentrations between PE complicated and non-PE complicated pregnancies [ 44 ]. The decrease in 25(OH)D status in late pregnancy among the PE group contrasts to the increase observed for the undiagnosed group, again emphasising the possibility that vitamin D is implicated in PE development in late gestation, independent of differences in the multiple mechanistic pathways of PE pathogenesis in early pregnancy [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective fully blinded cohort study of 257 pregnant women in an obstetric emergency service in Spain also found no association between SFlt-1/PIGF and 25(OH)D levels in women with PE. However, this study found a greater risk of late-onset PE among women with low 25(OH)D level (<50 nmol/L) (OR 4.6, 95% CI 1.4–15) and increased risk of both early- and late-onset PE when sFlt-1/PIGF ratios were above corresponding cut-points (ORs 58 [95% CI 11–312] and 12 [95% CI 5.0–27], respectively) [90]. …”
Section: Resultsmentioning
confidence: 99%
“…Studies reported varying degrees of risk for clinical subtypes of PE among women with low vitamin D levels [79, 90]. In order to guide the clinical recommendations, investigators must use a standard set of definitions for the disease and clinical subtypes in future research.…”
Section: Discussionmentioning
confidence: 99%